On the Ramanujan–Lodge harmonic number expansion - Mortici, Cristinel (2015)
The aim of this paper is to extend and refine the Ramanujan–Lodge harmonic number expansion into negative powers of a triangular number. We construct a faster asymptotic series and some new sharp inequalities for the harmonic numbers.